Maria [Beatriz] Barbosa de Souza : na gira da vida de Mãe Beata - Holmes, Karina Ceci de Sousa (2023)
Understanding personal collections as a sphere of infomemorial narratives that express an individual's life journey, involving their achievements and their relationships, the general objective of this research was to construct the infomemorial trajectory of Maria Beatriz, Mãe Beata, in the cultural, social and religious context of the city of João Pessoa (PB), starting from her personal collection, under the perspective of self-writing combined with the practices of escrevivência. As specific objectives this research aims to: a) to reflect on Mãe Beata's trajectory, considering the religious, cultural and social aspects, from the perspective of her personal collection; b) to characterize the documentation of Mãe Beata's personal collection, understanding it as a source of information and memory; c) to map Mãe Beata's religious, cultural and social relationships, based on oral testimonials from her family and her filhos de santo; d) to highlight her effective role in the development of Candomblé in Paraíba; and e) to compare oral and documentary information in the construction of Mãe Beata's religious infomemorial. The study is based on the guiding categories of: memory and information, self-writing (Foucault, 2009; Gomes, 2004) and escrevivência (Evaristo, 2017; 2020) as a theoretical-methodological basis. Escrevivência provided a kind of authorization for the interweaving of experiences of people who had similar individual and collective journeys, as well as contact with Mãe Beata, who had turned their trajectories into an armour against prejudice, intolerance and non-acceptance. The research is characterized as documental, with a qualitative approach, associated with narrative interviews of people linked either to their personal or religious conviviality, as well as information extracted from newspapers that have been distributed in Paraíba. Therefore, the results show that the records and trajectories of people who have been rendered invisible by time or by those who don't know their stories serve as supporting evidence/testimonies, providing the information needed to understand an entire historical and cultural journey. The trajectory of a black woman from the backlands of Brazil stands out, especially as regards of her contribution to Umbanda, Jurema and Candomblé Angola in João Pessoa/PB, whose memory is a source of wealth for religious cultural preservation (Silva, 2015). To record the trajectory of Mãe Beata is to be able to present some of her many struggles and achievements, such as the realization of marriage in Umbanda with civil effect in the 1970s. She was the one who established Candomblé Angola in João Pessoa and entered the academic field dressed in her axó (a ritualistic garment) at a time of notable conflicts and tyranny. Mãe Beata’s actions reveal her as a defender of the principles she believed in and also made it possible for the sounds of the elús and atabaques to be heard as an echo till today.